Stabilization of molecular lanthanide polysulfides by bulky scorpionate ligands12. Issue 25 (6th May 2016) - Kühling, Marcel; McDonald, Robert; Liebing, Phil; Hilfert, Liane; Ferguson, Michael J.; Takats, Josef; Edelmann, Frank T.
Abstract : The first well-defined lanthanide polysulfide complexes containing S4 2− and S5 2− ligands have been synthesized and structurally characterized by single-crystal X-ray diffraction. Abstract : Well-defined lanthanide polysulfide complexes containing S4 2− and S5 2− ligands, the samarium(iii ) pentasulfide complex Sm(Tp iPr2 )(κ 1 -3, 5- i Pr2 Hpz)(S5 ) and the tetrasulfide-bridged binuclear ytterbium(iii ) complex (μ-S4 )[Yb(Tp iPr2 )(κ 1 -3, 5- i Pr2 Hpz)(κ 2 -3, 5- i Pr2 pz)]2 (Tp iPr2 = hydro-tris(3, 5-diisopropylpyrazolyl)borate), have been synthesized and structurally characterized by single-crystal X-ray diffraction.